Enhancing hospital quality management and patient safety in Vietnam: a technical assistance project utilizing online solutions during COVID-19 pandemic - Jun Moriyama; Tomoo Ito; Masahiko Doi; Kaori Seino; Duong Huy Luong; Azusa Iwamoto; Hitoshi Murakami (Tropical Medicine and Health, 2022)
Abstract Since 2015, the National Center for Global Health and Medicine in Japan has been conducting a technical assistance project for improving patient safety in Vietnamese hospitals. During the COVID-19 pandemic, the project conducted a patient safety training program utilizing online solutions for participants from Vietnam. This resulted in an increase in the number of participants, and ensured access from remote locations. The convenience of easy access from smartphones encouraged further participation. In addition to online training, the utilization of platforms such as Facebook, a common social networking service in Vietnam, contributed to the dissemination of good practices.